O tempo como pena e o trabalho como prêmio: o cotidiano dos presos da Penitenciária Industrial Regional de Sobral (PIRS) - Carvalho, Robson Augusto Mata de (2009)
The objective of this research was to examine the relationship between the length of prison sentence and the prison work from the perspective of the prisoners of the Sobral Regional Industrial Penitentiary (PIRS). In order to understand this relationship, I analyzed the experiences of the perception of time and the sense of work in the socio-prison dynamic. Among the issues that guided the research are: how the individuals subjected to the disciplinary rules in PIRS perceive and experience the time of sentence? What are their representations of the time? How the prison spaces are distributed, appropriated and resignified by prisoners? What is the meaning of work for the prison way of life and the consciousness of the prisoners? Which sociability is made by the work? For technical and methodological procedures used during the field research, between the years 2007 and 2008, I made use of observations of the spaces and the relations between the social actors in prison, the analysis of institutional documents, local newspapers etc. Besides the observations, I’ve made semi-structured interviews with prisoners and people from the group leader in order to elucidate the network of social relations established in the institution. The research revealed that the time and work are appropriate and resignified the prisoners in a different way of the outside society. In a idleness’ context , the time presents itself as a significant daily category, since the prisoners have their own formulations about the time they spend in prison, as "lost time", "dead time", "kill time" etc. As scarce goods, the work appears with one of the best ways to "spend time" and to achieve "recovery", contributing to the formation of expectations, desires, relationships, behavior, forms of organization and sociability.